2005
DOI: 10.1111/j.1085-9489.2005.10305.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on thermal and vibratory thresholds of quantitative sensory testing

Abstract: Quantitative sensory testing has become a common approach to evaluate thermal and vibratory thresholds in various types of neuropathies. To understand the effect of aging on sensory perception, we measured warm, cold, and vibratory thresholds by performing quantitative sensory testing on a population of 484 normal subjects (175 males and 309 females), aged 48.61 +/- 14.10 (range 20-86) years. Sensory thresholds of the hand and foot were measured with two algorithms: the method of limits (Limits) and the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
114
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 67 publications
19
114
1
5
Order By: Relevance
“…Lin et al [23] reported a significant effect of gender on vibration threshold measured at the lateral malleolus. However, the authors neither mentioned the direction of this relationship nor did they control for height differences between men and women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lin et al [23] reported a significant effect of gender on vibration threshold measured at the lateral malleolus. However, the authors neither mentioned the direction of this relationship nor did they control for height differences between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Since quantitative sensory testing captures the overall function of the sensory neuroanatomical circuitry, age-related decline detected in our study could potentially arise from deterioration in multiple components of the sensory pathway, ranging from structural deformation and reduced density of sensory receptors to degraded information processing in the somatosensory cortex [23]. Studies investigating aging effects on spatial and temporal summation characteristics of the P channels that are mediated by Pacinian corpuscles and their corresponding nerve fibers suggest that the primary factor responsible for elevation in the detection thresholds of high frequency vibration in older subjects is a reduced afferent input to central nervous system (CNS) [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers such as Dyck et al (1987a, b), Adams et al (1989), and Lin et al (2005) have all shown changes in light touch, pinprick, deep pressure, vibration, and even temperature perception during aging as well as in some disease conditions. These confounding effects were eliminated in this study by limiting our choice of participants to young males of Asian origin.…”
Section: Participantsmentioning
confidence: 99%